2019
DOI: 10.1002/hbm.24909
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the global orientation bias of the visual system changes population receptive field elongations

Abstract: The topographical structure of the visual system in individual subjects can be visualized using fMRI. Recently, a radial bias for the long axis of population receptive fields (pRF) has been shown using fMRI. It has been theorized that the elongation of receptive fields pointing toward the fovea results from horizontal local connections bundling orientation selective units mostly parallel to their polar position within the visual field. In order to investigate whether there is a causal relationship between orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 63 publications
(85 reference statements)
3
24
0
Order By: Relevance
“…Through simulation we identify methods for improving sensitivity that may estimate ellipses with smaller aspect ratios. The results we present are quantitatively consistent with assessments using several other methodologies (Greene et al, 2014; Zeidman et al, 2018; Merkel et al, 2020).…”
supporting
confidence: 89%
See 4 more Smart Citations
“…Through simulation we identify methods for improving sensitivity that may estimate ellipses with smaller aspect ratios. The results we present are quantitatively consistent with assessments using several other methodologies (Greene et al, 2014; Zeidman et al, 2018; Merkel et al, 2020).…”
supporting
confidence: 89%
“…For example, Merkel et al (2018; 2020) estimated the aspect ratios of voxels in early visual cortex and reported ellipticity (the inverse of aspect ratio) ranging between 0.6 and 1, which corresponds to aspect ratios of 1 to 1.67 (Figure 7A; Merkel et al, 2020). Using tomographic methods to estimate pRF shapes (Greene et al, 2014) also estimated aspect ratios (Figure 7B).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations